The new English curriculum : a study of text complexity in reading and written English : a thesis submitted as partial fulfilment of the requirements for the degree of Master of Education, Massey University - Capper, Hilary (Massey University, 1998)
This research examines the teaching methods in a Year 7 distance education English programme in relation to text complexity in reading and written English. It considers student performance, processes, resources and teaching strategies. The research focuses on the assessment and teaching of text complexity in reading and written English in relation to student aptitude. It explores how the students' needs were met in the years 1996-1997 and considers the implications for teachers of the new English curriculum in relation to the assessment and teaching of text complexity. Consideration is also given to criticism of the new English curriculum especially where it is relevant to the teaching of text complexity in reading and written English. The thesis therefore has two aspects to it. Firstly the criticisms of the new curriculum and the English curriculum, in particular, are examined and the implications these criticisms may have for the teaching of text complexity are considered. Secondly a Year 7 English programme developed in distance mode at The Correspondence School is researched in light of the requirements of the new English curriculum as it relates to text complexity in reading and written English.
Keywords: English language study; Curriculum-based assessment; Student rating; English learning